Studying the Geroprotective Properties of YAP/TAZ Signaling Inhibitors on Drosophila melanogaster Model. - Golubev, D.A.; Zemskaya, N.V.; Gorbunova, A.A.; Kukuman, D.V.; Moskalev, A.; Shaposhnikov, M.V. (International journal of molecular sciences, 2023)
The transcriptional coactivators Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) are the main downstream effectors of the evolutionarily conserved Hippo signaling pathway. YAP/TAZ are implicated in the transcriptional regulation of target genes that are involved in a wide range of key biological processes affecting tissue homeostasis and play dual roles in the aging process, depending on the cellular and tissue context. The aim of the present study was to investigate whether pharmacological inhibitors of Yap/Taz increase the lifespan of Drosophila melanogaster. Real-time qRT-PCR was performed to measure the changes in the expression of Yki (Yorkie, the Drosophila homolog of YAP/TAZ) target genes. We have revealed a lifespan-increasing effect of YAP/TAZ inhibitors that was mostly associated with decreased expression levels of the wg and E2f1 genes. However, further analysis is required to understand the link between the YAP/TAZ pathway and aging.